Eco-Innovations in The Context of Creating More Sustainable Economies - Marija KUSTELEGA; Magdalena KUSTELEGA; Tamara SMAGUC (Communications of International Proceedings, 2022)
The paper discusses the importance of eco-innovations for sustainable development and the creation of a more competitive economy. This paper aims to show the state and trends related to eco-innovations in Croatia compared to average data for the European Union, and thus pave the way for comprehensive empirical research in this area. At the beginning of the paper, the theoretical framework of eco-innovations is given in the form of definition, role, as well as drivers and obstacles to their adoption. The second part of the paper analyzes and compares the results achieved by Croatia in relation to the average for the European Union. Also, the results for Croatia are compared with the results for Slovenia, as a comparative neighboring country. The results indicate an interesting trend according to which the countries ranked among the leaders in ecological innovations invest significantly in the research and development of eco-innovations, which is mostly financed by state funds. This is also confirmed by the example of Slovenia, where an increase in the ranking of eco-innovators has been recorded in the last few years, mainly due to the state's activities and increased investment in research and development. Croatia achieves the weakest results in this area. Therefore, the index could be significantly improved if the state intervened with appropriate measures.
Keywords: eco-innovations; circular economy; sustainable development; Croatia